Optimization of Near-Infrared Fluorescent Sentinel Lymph Node Mapping in Cervical Cancer Patients. Issue 8 (1st November 2011) - van der Vorst, Joost R.; Hutteman, Merlijn; Gaarenstroom, Katja N.; Peters, Alexander A. W.; Mieog, J. Sven D.; Schaafsma, Boudewijn E.; Kuppen, Peter J. K.; Frangioni, John V.; van de Velde, Cornelis J. H.; Vahrmeijer, Alexander L.
Abstract : Objective: In early cervical cancer, a total pelvic lymphadenectomy is the standard of care, even though most patients have negative nodes and thus undergo lymphadenectomy unnecessarily. Although the value of sentinel lymph node (SLN) mapping in early-stage cervical cancer has not yet been established, near-infrared (NIR) fluorescence imaging is a promising technique to perform this procedure. Near-infrared fluorescence imaging is based on invisible NIR light and can provide high sensitivity, high-resolution, and real-time image guidance during surgery. Methods: Clinical trial subjects were 9 consecutive cervical cancer patients undergoing total pelvic lymphadenectomy. Before surgery, 1.6 mL of indocyanine green adsorbed to human serum albumin (ICG:HSA) was injected transvaginally and submucosally in 4 quadrants around the tumor. Patients were allocated to 500-, 750-, or 1000-μM ICG:HSA concentration groups. The Mini-FLARE imaging system was used for NIR fluorescence detection and quantitation. Results: Sentinel lymph nodes were identified in all 9 patients. An average of 3.4 ± 1.2 SLNs was identified per patient. No differences in signal to background of the SLNs between the 500-, 750-, and 1000-μM dose groups were found ( P = 0.73). In 2 patients, tumor-positive lymph nodes were found. In both patients, tumor-positive lymph nodes confirmed by pathology were also NIR fluorescent. Conclusions: This study demonstrated preliminary feasibility to successfully detect SLNs in cervical cancer patients using ICG:HSA and the Mini-FLARE imaging system. When considering safety, cost-effectiveness, and pharmacy preferences, an ICG:HSA concentration of 500 μM was optimal for SLN mapping in cervical cancer patients.